PENGARUH MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA VIDEO ANIMAKER TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIS SISWA SD - Shafa Kamila Putri Anggraini; Erna Suwangsih; Nenden Permas Hikmatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Understanding mathematical concepts is an important skill that students must have in learning mathematics. However, in reality, there are still many elementary school students who have difficulty in understanding mathematical concepts due to inappropriate learning approaches and unattractive media. Therefore, this study aims to determine the influence and improvement of students' understanding of mathematical concepts, one of which is by implementing the Teams Games Tournament (TGT) model assisted by video animaker media. The method used in this study is a quasi-experiment with a non-equivalent control group design and purposive sampling technique. This study compares two classes, namely the experimental class and the control class. Data collection was carried out through an initial test (pretest) and a final test (posttest), and was supported by observation and documentation. Based on the results of the study, the Teams Games Tournament (TGT) model assisted by video animaker media is more effective in improving students' understanding of mathematical concepts when compared to conventional learning. The Teams Games Tournament (TGT) model assisted by video animaker media has an influence of 45.5% in influencing the improvement of students' understanding of mathematical concepts.